The beloved land eaudiobook Song of acadia series, book 5. - Oke, Janette (Song of Acadia, 2012)
The best-selling Song of Acadia series follows the affairs of two sisters, from the French expulsion from Nova Scotia to the turmoil of the American Revolution. Anne in England and Nicole in America are separated by an ocean, but their hearts are still close. When they each receive a letter, they are suddenly called on a perilous journey back to their beloved homeland.